Standardisation of plant part as an index of potassium status in Banana, Musa (AAB Group) Nendran - Sumam George (Department of Soil Science and Agricultural Chemistry, College of Agriculture, 1994)
A field experiment in Musa (AAB group) Nendran, the most popular commercial fruit crop of Kerala was undertaken from August, 1991 to May, 1992 with seven graded levels of K as treatments replicated thrice. The soil, medium in N and P and high in K status belonged to the taxonomic class ‘loamy kaolinitic isohyperthermic aeric tropic fluvaquents’. The effects of higher levels of K on all important growth characters of the crop like height of pseudostem, girth of pseudostem at different heights from the ground level, total number of leaves, number of functional leaves, total leaf area, leaf area index and total dry matter production were more pronounced from the shooting stage of the crop after the plants had received the full dose of K supply. Uptake of major nutrients N, P and K showed increasing trend with increase in K supply. Uptake of Ca showed a negative relationship with increasing K application while Mg uptake showed an inconsistent pattern. Uptake of micronutrients Fe, Mn, Cu and Zn were maximum at K3 level of application (225 g K2O plant-1). Soil content of available K increased while exchangeable Ca and Mg contents decreased at higher levels of K supply. The maximum bunch yield of 26.18 t ha 1-which was significantly higher than all other treatments was recorded at K3 level (225 g k2O plant-1) This level also resulted in maximum values for all the yield attributing characters like number of hands bunch-1, number of finger bunch-1, weight of hand, length of finger, girth of finger and weight of finger. By adopting this recommendation a net fertilizer saving of 75g K2O plant-1 Can be achieved which is equivalent to 312.5 kg of muriate of potash costing Rs. 2000 at the present market rate. Over and above this, increase in yield obtained by doing so is 4500 kg ha-1. Additional income that could be generated by the way of sale of this at the rate of Rs. 8 kg-1 works out to Rs. 36000. Thus a total saving of Rs. 38000 ha-1 can be achieved by following the suggested recommendation. Path coefficient analysis of yield attributes showed that the character number of finger bunch-1 is having the maximum direct effect on yield followed by girth of fruit and weight of fruit. Quality characters of the fruit namely total and non reducing sugars, shelf life and flesh peel ratio showed significant and positive trend towards K nutrition. Correlation coefficient were worked out between bunch yield and important crop characters. Balance sheet of nutrients in soil after harvest of the crop was worked out to assess the final soil status of nutrients in relation to the initial status. Petiole of the third leaf up to shooting stage of the crop and that of the flag leaf there after was selected as the index of K status of the plant as the K content of the same was found to hold the maximum relationship with bunch yield at all the growth stages. The critical K levels in the petiole for maximum yield as well as maximum response to fertilizer application at each stage were determined which were found to be 1.30 per cent and 1.02 per cent respectively at early vegetative stage, 1.28 per cent and 1.06 per cent respectively at late vegetative stage, 1.80 per cent and 1.36 per cent respectively at shooting stage, 2.43 per cent and 1.98 per cent respectively at post shooting stage, 2.50 per cent and 1.80 per cent respectively at bunch maturation stage and 2.47 per cent and 1.80 per cent respectively at harvest stage. The critical K content in soil for economic yield worked out to 286.5 kg K2O ha-1 at early vegetative stage, 276.5 kg K2O ha-1 at late vegetative stage, 271.o kg K2O ha-1 at shooting stage, 239.o kg K2O ha-1 at post shooting stage, 245.0 kg K2O ha-1 at bunch maturation stage and 236.0 kg K2O ha-1 at harvest stage. Graphs were plotted relating petiole K content to soil K content at important growth stages of the crop based on quadratic regression models to provide information on soil K content at a particular stage if the petiole K content at that stage is known. Linear regression models were developed relating soil K content to fertilizer dose to find out the quantity of fertilizer to be applied to bring the soil level to the critical level.